Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-05-22T19:48:17+02:00
Bonjour, 

I/ Développer et réduire D 

D = (2x - 3)(5 - x )+(2x - 3)²
D= 10x - 2x² - 15 + 3x + 4x² - 12x + 9
D= 2x² + x - 6

II/ Factoriser D

D = (2x - 3)(5 - x )+(2x - 3)²
D= (2x - 3)(5 - x + 2x - 3)
D= (2x - 3)(x + 2)

III/ Résoudre l'équation (2x - 3)(x + 2) = 0

Un produit est nul si un de ses facteur est nul.
(2x - 3)(x + 2) = 0
2x - 3 = 0 ou x + 2 = 0
2x = 3 ou x = - 2
x = 3/2 ou x = - 2

S= {- 2 ; 3/2}

Bonne soirée! =)
2014-05-22T19:51:42+02:00
Bonsoir

Développement

D = 10x - 2x² -15 +3x + 4x² - 12x +9
D = 2x² +x - 6

factorisation
D = (2x-3)(5-x-+2x-3)
D = (2x-3)(x +2)

D = 0
soit 2x - 3 = 0 donc 2x = 3 et x = 3/2
soit x +2 = 0 et x = -2